2021
DOI: 10.21930/rcta.vol23_num1_art:2032
|View full text |Cite
|
Sign up to set email alerts
|

Callogénesis in vitro de durazno (Prunus persica L.) var. Huayco rojo a partir de explantes foliares

Abstract: El durazno (Prunus persica L.) presenta en la actualidad gran importancia económica para el Perú, el incrementar su exportación cada año, siendo la variedad Huayco rojo el de mayor producción y exportación por presentar un agradable sabor y gran aceptación en el mercado exterior. En la búsqueda de expandir las áreas de este cultivo se han realizado estudios de multiplicación empleando métodos biotecnológicos como la micropropagación in vitro, pero se han presentado problemas con esta especie por ser de comport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Similarly, the results obtained were superior to those obtained by Koleva et al 27 The growth regulator 2,4-D is added to the culture media to induce the proliferation of undifferentiated cells, forming the characteristic cell mass called callus 28 . The 2,4-D has a rapid induction effect initially at the edges of the initial explant until it covers the entire structure, depending on the concentrations, combinations with other growth regulators, initial explant and the species with which the research is being carried out [29][30][31] . From this embryogenic callus, it was possible to observe the formation of somatic embryos after 12 weeks in the culture medium, concerning the fact that some species have the characteristic of the formation of somatic embryos after the formation of callus (indirect somatic embryogenesis), and likewise, remaining in the same culture medium without changing it or refreshing the medium 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the results obtained were superior to those obtained by Koleva et al 27 The growth regulator 2,4-D is added to the culture media to induce the proliferation of undifferentiated cells, forming the characteristic cell mass called callus 28 . The 2,4-D has a rapid induction effect initially at the edges of the initial explant until it covers the entire structure, depending on the concentrations, combinations with other growth regulators, initial explant and the species with which the research is being carried out [29][30][31] . From this embryogenic callus, it was possible to observe the formation of somatic embryos after 12 weeks in the culture medium, concerning the fact that some species have the characteristic of the formation of somatic embryos after the formation of callus (indirect somatic embryogenesis), and likewise, remaining in the same culture medium without changing it or refreshing the medium 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A balance between auxins and cytokinins leads to callus development [61]. However, multiple research works have reported that the use of 2,4-D induces in vitro callus formation from various explants, positioning it as one of the regulators that better promotes the callus formation, whether or not it is combined with cytokinins [62][63][64][65].…”
Section: Experimental Phase 2: Callus Formation Protocolmentioning
confidence: 99%
“…A balance between auxins and cytokinins leads to callus development [54]. However, multiple research works have reported that the use of 2,4-Dichlorophenoxyacetic acid (2,4-D) induces in vitro callus formation from various explants, positioning it as one of the regulators that better promotes callogenesis, whether, or not it is combined with cytokinins [55][56][57][58].…”
Section: Experimental Phase 2: Callogenesis Inductionmentioning
confidence: 99%